The Impact of Compensation and Career Development on Employee Performance at PT. XYZ - Kurnia Solehah; Yudi Kristanto; Setiawati (ITQAN: Journal of Islamic Economics, Management, and Finance, 2026)
This research is motivated by the emergence of problems related to compensation and career development disparities among permanent employees, contract employees, and outsourced employees. The purpose of this study is to determine the effect of compensation and career development on employee performance. This study uses a quantitative method with a stratified random sampling technique conducted at PT. XYZ conducted a study with a sample of 165 people, utilizing a data collection technique involving a questionnaire. Data analysis techniques using SPSS include instrument testing (validity and reliability tests), analyst prerequisite tests (normality and homogeneity tests), and statistical hypothesis testing (product-moment correlation tests and linear regression tests). Based on the results of the t-statistical test, there is a partial effect of compensation (X1) on employee performance (Y), as marked by the calculated t-value of 13.787, which exceeds the t-table value of 1.970. Additionally, there is a partial effect of career development (X2) on performance (Y), as indicated by the calculated t-value of 17.642, which exceeds the t-table value of 1.970. The sig. Value. F Change of 0.000 < 0.05 concludes that the compensation variables (X1) and career development (X2) simultaneously have a significant relationship with employee performance (Y).